2019
DOI: 10.1002/trtr.1795
|View full text |Cite
|
Sign up to set email alerts
|

Play(ful) Pedagogical Practices for Creative Collaborative Literacy

Abstract: In action research projects, creative, play, and collaborative activities intersect with early writing experiences in kindergarten and grades 1 and 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In the subset of structural emergent properties, we mainly identified pedagogical approaches for creative writing that explored primary school learning and teaching (Christianakis, 2011a;Christianakis, 2011b;Coles, 2017;DeFauw, 2018;Hall & Grisham-Brown, 2011;Portier et al, 2019;Rumney et al, 2016;Sears, 2012;Steele, 2016;Southern et al, 2020;Yoo & Carter, 2017). These pedagogical approaches were aimed at addressing issues related to personal emergent properties such as motivation and engagement, and confidence in writing.…”
Section: Structural Emergent Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the subset of structural emergent properties, we mainly identified pedagogical approaches for creative writing that explored primary school learning and teaching (Christianakis, 2011a;Christianakis, 2011b;Coles, 2017;DeFauw, 2018;Hall & Grisham-Brown, 2011;Portier et al, 2019;Rumney et al, 2016;Sears, 2012;Steele, 2016;Southern et al, 2020;Yoo & Carter, 2017). These pedagogical approaches were aimed at addressing issues related to personal emergent properties such as motivation and engagement, and confidence in writing.…”
Section: Structural Emergent Propertiesmentioning
confidence: 99%
“…A study by Portier et al (2019) investigated approaches to teaching writing that were motiving and engaging for students. Involving 10 northern rural communities in Canada, the project implemented collaborative, play(ful) learning activities alongside sixteen teachers and their students.…”
Section: Play(ful) Activities Visual Arts and Dramamentioning
confidence: 99%
“…Play research has found teachers want clear guidance for mediating play and integrating literacy effectively (Neaum, 2020; Pyle et al, 2018; Rand & Morrow, 2021). Portier et al (2019) offer helpful K–2 teacher mediation strategies for literacy play curricular activities. However, teachers sometimes lack clarity on their role within play, specifically how and when to get involved in children's play (Meacham & Han, 2021).…”
Section: A Framework For Integrating Play and Literacymentioning
confidence: 99%
“…Portier et al (2019), however, observe that regardless of the affordances of playful learning, play in early childhood education has been hindered by an emphasis on teaching the basics of literacy and a focus on standards‐based education. They claim that early‐years teachers feel strained and struggle to integrate play into pedagogical practices that emphasize more teacher structured approaches to academics to meet curricular expectations.…”
Section: Science Learning Through Play: Linking Theories and Classroom Practicesmentioning
confidence: 99%